MARRIAGE CRISIS AMONG MILLENNIALS IN THE DIGITAL ERA: An Etnographic Study on TikTok and Islamic Family Law Perspectives - Putra, Yulizain; Bahar, Muchlis; Kholidah; Azwar, Zainal (Jurnal Studi Islam dan Sosial, 2025)
The rapid development of digital technology has significantly influenced social dynamics, particularly the institution of marriage among the millennial generation. This study aims to examine the marriage crisis in the digital era through a netnography approach on TikTok, a popular social media platform among millennials. The netnographic method was employed to analyze content, interactions, and narratives about marital issues shared by TikTok users. Findings reveal that digitalization has brought significant changes in communication, expectations, and conflict resolution among spouses, often leading to crises and divorces. Social media also functions as a public space that expands discourse on marriage issues but may exacerbate problems due to the spread of inaccurate information. This study assesses the relevance of these findings to family law in Indonesia, especially concerning the protection of the rights of spouses and children in the context of modern marriage. The study recommends updating family law policies to be more responsive to challenges in the digital era to ensure healthy and fair marital continuity. Therefore, this research contributes valuable insights to family law studies and the social dynamics of digital millennials.